The gift of science. Leibniz and the modern legal tradition. - Berkowitz, Roger, 1968- (Harvard University Press, 2005)
Moving from the scientific revolution to the nineteenth-century rise of legal codes, Berkowitz tells the story of how lawyers and philosophers invented legal science to preserve law's claim to moral authority. The "gift" of science, however, proved bittersweet. Instead of strengthening the bond between law and justice, the subordination of law to science transformed law from an ethical order into a tool for social and economic ends.